Alive Animal Model for Epilepsy by Intradorsal Striatum Injection of Colchicine - Fakhroleslam, Zahra; Karami, Manizheh; Roghani, Mehrdad; Nejadebrahim, Atiyeh (International Journal of Epilepsy, 2021)
Background Epilepsy is a neural disorder with repeatable seizure attacks. In this article, we used the neurotoxin colchicine, which is derived from the plant Colchicum autumnale, to introduce a low cost but the more valuable alive animal model for epilepsy.Materials and Methods Wistar rats weighing 250 to 300 g after intraperitoneal injection of ketamine (100 mg/kg) and xylazine (20 mg/kg) were restrained in the stereotaxic apparatus; they were cannulated in the dorsal striatal area (AP: 0.5 mm; L: 3 mm; V: 3.6 mm). One week later, an injection cannula attached to a 5-µ Hamilton syringe by polyethylene tubing guided 0.05 to 25 μg/rat colchicine in the recovered healthy rats once daily for 4 consecutive days. The control group solely received the saline solution. The behavioral signs of all animals were daily recorded. Finally, the brains of rats under deep euthanasia were collected in 10% formalin and examined histopathologically. The dorsal striatal regions were cut coronally into 3 to 4 µm-thick slices, and then stained with hematoxylin-eosin. They were eventually examined under the light microscope to verify the injection placement or possibility of lesions. All data were analyzed by analysis of variance under α = 0.05.Results Behaviors were quantified based on Racine five-stage scoring and showed the significant epileptic generalized seizures in alive animal treated by intrastriatal injection of colchicine. However, tissue damage was invisible in the target brain area.Conclusion The colchicine, using injection successively into the dorsal striatal region of rat, can create recurring epileptic convulsions in the animal.
Keywords: epilepsy; colchicine; dorsal striatal region; alive; rat